English proficiency of Japanese third-age learners in the English foreign language program: an explanatory-sequential inquiry - San Jose, Dominic Bryan S.; Guitche, Melona Q.; Madrigal, Dennis V. (Penerbit Universiti Kebangsaan Malaysia, 2024)
English as a Foreign Language (EFL) empowers individuals from non-English-speaking countries to acquire English proficiency and opens the doors to countless opportunities. This applies to Japanese third-age learners enrolled in EFL programs for various reasons. However, EFL teachers face challenges in tailoring programs to the diverse needs of third-age learners. Using explanatory sequential inquiry, this study assessed the English proficiency level of Japanese third-age learners engaged in the EFL programs in five cities in Japan. The quantitative phase revealed that the English language proficiency (ELP) level of Japanese third-age learners as a whole is B1 or Intermediate. The rank biserial correlation coefficient shows a significant relationship between sex and ELP. The Spearman rank correlation shows a significant relationship between the third-age learners' ELP and age, educational background, and hours spent learning English per week. The qualitative phase revealed an affirmation of the quantitative findings through the two major themes (motivational factors and factors affecting ELP) generated from the participants' thick descriptions of their experiences. Integrating quantitative and qualitative findings resulted in several meta-inferences and emerging frameworks. It concluded that the ELP development among third-age learners is multifaceted. The complex interplay of sex dynamics, cultural norms, age, motivation, experiences, and learning mechanisms in promoting ELP must be considered. Lastly, the findings served as a foundational reference for designing and developing instructional materials (IMs) for Japanese third-age learners, potentially enhancing their EFL learning experience.